Mulheres negras idosas: a invisibilidade da violência doméstica - Oliveira, Ilka Custódio de (2016)
The differences experienced by social classes throughout the life cycle draw different old ages. It is not a homogeneous process, rich and poor do not experience it the same way. Aging is a social problem to the working class which, possessing only its labour force, when old, loses the usage value to the capital and is tackled, once again by the social depreciation and poverty, becoming more sociably invisible as it gets older. Aging carries the social inequalities experienced throughout life. The black population, due to racism and its ramifications, has a life with more disadvantages than the white population; aging is a harder experience to the black population. Women live longer than men do, but if we were to add to the group of social inequalities fostered by racism gender inequalities, black women aging is even more challenging. The comprehension of linking between aging, racism and gender can be made from domestic violence, understood as a violation of human rights, which derives from a social organization, which favours male to the detriment of female. The empirical research was performed in a judgement of Domestic and Familiar Violence against women in the Court of Justice of São Paulo, having as analysed material the psychosocial expertise carried out with elderly women, in the period from January 2014 to November 2015. The sample was composed of 11 elderlies, from which 4 were black and 7 were white. The analysis has evinced that psychosocial expertise are tools that have elucidated the magnitude of the domestic violence situation in which these elderly were inserted into and that they experienced unseeing social practices, which imprisoned them in the domestic violence circuit, not allowing aging to be lived with dignity